Autonome comme si vous l’étiez - Gérard Dubey (La Nouvelle Revue du Travail)
One of digital machines’ main attributes is the way they split the meaning of sense (the attribution of finalities). This is a quantum leap from a past analogical phase where – through sensations and feedback effects – users could find themselves fully materialised in the realities that they interpret. Today’s automation phase has defined itself as a search for ways of compensating for some of the effects of this disconnect, without questioning its theoretical preconceptions. In this new context, which exists outside of a work framework, automation plays the role of a new “natural” environment, with action becoming the way of adapting to this.In consideration of the above points and based on 25 years of aeronautical experience, the study seeks to reconsider or redefine the notion of autonomy at work.